PELATIHAN PENGOLAHAN BAHAN PANGAN LOKAL IKAN TONGKOL MENJADI ABON DI NUSA LEMBONGAN-BALI - Ni Putu Eka Trisdayanti; AA. Gd. Putra K.P. Dalem; Made Hendrayana (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
This community service aims to provide training in processing local tuna to be shredded in Nusa Lembongan. Based on the analysis of the situation and needs, it is known that many local tuna foodstuffs have not been used optimally. Tuna that is not sold out, rotten and thrown away. Based on this, it is important to carry out a training program regarding the processing of tuna into floss. Apart from being for the community, shredded tuna is later expected to become a culinary tourism product. The methods used in this training session were theoretical lectures on tuna and its potential, cooking demonstrations, and hands-on practice for the participants. The evaluation results showed that the participants were enthusiastic about participating in the training and were able to practice the shredded tuna processing method.